Diagnostic Value of Frequently Implemented Provocative Tests in the Assessment of Shoulder Pain—A Glimpse of Current Practice - Nahum Rosenberg (Medicina, 2021)
Initial evaluation of chronic shoulder disability is a diagnostic challenge due to the anatomic complexity of the shoulder joints. For this purpose, several diagnostic tools utilizing provocative testing exist, but only a few have a reliable basis for their diagnostic value. Therefore, objectively determining the predictive value of these tests in identifying the precise anatomical source for disability—subacromial, intraarticular or other—is essential in order to proceed with further imaging evaluations for final objective diagnoses. Using validated clusters of provocative tests should improve their diagnostic values.